Cryopreservation of Shoot Tips of Elite Cultivars of Cannabis sativa L. by Droplet Vitrification - Esther Uchendu; Hemant Lata; Suman Chandra; Ikhlas A. Khan; Mahmoud A. ElSohly (Medical Cannabis and Cannabinoids)
Cannabis sativa L. (marijuana or hemp) is recognized worldwide for its psychoactive properties as well as for fiber production. This study focused on the evaluation of 3 droplet vitrification protocols for long-term conservation of shoot tips in liquid nitrogen (LN). Shoot tips (∼0.5 mm) were excised from 3- to 4-week-old in vitro-grown shoots of 3 cultivars (MX, VI-20, and B-5: high tetrahydrocannabinol [THC], high cannabidiol [CBD], and intermediate THC∼CBD, respectively) and pretreated on 5% dimethyl sulfoxide agar plates for 48 h. The shoot tips were then vitrified in LN using 3 separate cryoprotectant (plant vitrification solutions [PVS] #2, #3, and #4) droplets on an aluminum cryoplate. There was no significant difference between the regrowth of cryopreserved shoot tips exposed to PVS2 for 15 and 20 min, but regrowth of all 3 cultivars significantly declined after 20 min of exposure. Exposure duration of 15 min was adapted for subsequent experiments. Regrowth of cryopreserved MX was significantly higher with PVS2 (63%) than with PVS3 and PVS4 (≤5%). Regrowth of cryopreserved VI-20 was highest with PVS2 (57%) and significantly higher than with PVS3 and PVS4 (≤25%). The regrowth of cryopreserved shoot tips of B-5 was significantly different between all 3 protocols with PVS2 > PVS4 > PVS3. Both PVS2 and PVS4 produced regrowth above 55%, while regrowth with PVS3 was significantly lower (31%). These results indicate that 15–20 min of exposure to PVS2 are most suitable for cryopreservation of these varieties. This is the first report on protocol development for the cryopreservation of organized tissues of C. sativa L. for germplasm conservation.